Locke's Ethics of Virtuous Thinking - Thébert, Angélique (Locke Studies)

(untitled) (Western Libraries at The University of Western Ontario, 2022)
Locke is generally taken as promoting an ethics of belief. For him, we must apply a doxastic norm so that we properly conduct our understanding. Thus, he forcefully highlights one key epistemic norm, the norm of evidence, that prescribes that we adjust the strength of our assent to the available evidence. I shall argue that Of the Conduct of the Understanding constitutes the framework within which Locke’s remarks in the Essay must be inserted. Far from promoting a mere ethics of belief, Locke actually promotes a virtue epistemology, or an ethics of virtuous thinking. Contrary to doxastic anti-voluntarism, this new way of apprehending Locke’s remarks does not downplay the role of the will. But compared to doxastic voluntarism, it gives its due role to the will (it is not devoted to the control of our assent, but to the ordering the consideration of an idea, or the forbearing to consider it, which is at the bottom of the acquisition of intellectual habits). Moreover, it takes into account important aspects of our intellectual life, namely diachronic and social aspects.